DIFFERENCE BETWEEN MUSCLE ACTIVITIES DURING JUMPING MOTION IN DESCENT AND ASCENT PHASES ON A TRAMPOLINE - MASAHARU MATSUSHIMA (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
Trampoline bounces are performed on a bed of a jumping surface that is stretched over the trampoline apparatus. The jumping motion is divided into a descent phase, i.e., from the landing to the maximum depth, and an ascent phase, from the maximum depth to the takeoff. Most studies on muscle activity during jumping have investigated muscle activity during the same phase between groups or between landing and release; however, no studies have investigated muscle activity between phases. Therefore, this study aimed to investigate muscle activity during the descent and ascent phases and obtain basic data on the jumping motion. For the trials, participants were instructed to perform 15 consecutive jumps on the trampoline bed from a standing still position, as high as possible, straight and straight up in the center of the trampoline bed. The muscle activities of the rectus femoris, tibialis anterior, and lateral gastrocnemius revealed significant increases and larger effect sizes in the descent phase than in the ascent phase (p < 0.01). The muscle activities of the sternocleidomastoid, trapezius, and biceps femoris demonstrated significant increases and medium effect sizes in the descent phase in contrast to the ascent phase (p < 0.01). Pushing down the bed by the muscular activity of the lower extremities is most pursued in the descent phase. Then, participants maintain a straight vertical posture for the body to receive the rebound force from the maximum depth of the bed. This suggests that the sternocleidomastoid and trapezius muscles were significantly active in controlling the head position. A high jump is achieved by pushing the bed down for a deep descent and maintaining a straight posture at the maximum depth. The elastic bed is similar to an Open Kinetic Chain in the descent phase because the load incrementally increases, and to a Closed Kinetic Chain in the ascent phase because the load begins at the maximum depth of the bed. Separating the elements of the jumping motion required in the descent and ascent phases is important in athletic training